Health problems and risky health behaviors among elderly people of Baluwa VDC of Kathmandu district. - Koirala, Sangeeta (2013)
SUMMARY: This study was conducted in Baluwa VDC of Kathmandu District. The study type used was cross-sectional descriptive study. Simple random sampling was done to identify the sampling frame. The respondents were identified using lottery method with the help of VDC staffs. The main objective of the study was to identify the health problems and risky health behaviors among the study group of the study area. The study duration was 6 weeks. Quantitative data were collected by using structured and semi-structured interview schedule. Data entry and analysis was done using SPSS window version 16.0 and Ms-Excel. Sample size of the study was 111 among which 28.8% respondents are in the age group 60-65. Female respondents are more than male i.e. 54.05%. More than half of the respondents i.e. 55.86% are married and 53.2% live their husband/wife. The current occupation of 67.6% family is occupation. Previous occupation of 75.7% respondents was agriculture. 71% of the respondents have land ownership, 48% are engaged in some kind of income generating activities and 91% respondents participate in social activities. 31.5% of the respondents take major family decisions. 33.3% of the respondents smoke tobacco product or hukka. 12.6% drink alcohol on daily or weekly basis and 9.9% of the respondents chew tobacco regularly. 91% of the respondents have good ability of conversation, 82% respondents have good hearing and 62.2% respondents have good vision. 71.2% respondents have presence of chronic disease. 16.45% have asthma, 16.45% have heart disease, 40.50% have gastritis, 21.51% have hypertension, 7.59% have diabetes, 32.91% have joint related problems, 3.79% have swelling of limbs, 1.26% has tuberculosis and 10.12% have other diseases like piles, allergy, tumor etc. Among the respondents who have chronic disease, 24.04% lie in age group 60-64 years, 60.26% are female and almost 80% were previously engaged in agriculture. Majority don't have risky health behavior, majority have good ability to do conversation, visual capacity and hearing capacity. Only 9.9% of the respondents feel lonely very less, 57.7% are satisfied with their life, 77.5% feel helpless sometimes and 9% feel helpless very often. 73% of the respondents feel being abused by their family members sometimes and 4.5% feel being abused very often. 90.7% of the respondents feel economically abused, 65.1% feel mentally abused, 15.1% feel socially abused and 5.8% feel physically abused. Among the respondents who have chronic disease, majority feel loneliness, helplessness and abused sometimes by their family members. However, majority of them were satisfied with their life. Majority of the respondents can perform activities of daily living (ADL) by themselves. More respondents are dependent upon others for instrumental activities of daily living (IADL) like travelling by public transportation, shopping for groceries, doing household work, preparing meals and taking medicine.